A Brief Description of the Music of the Tajiks in China - Yaqin Zhang (Art and Society, 2023)
The Tajiks have a long history, and the term “Tajik”, which translates as “crown” in Persian, is widely recognised by the Tajiks in our country. According to evidence, in several centuries BC, the ancestors of the Tajiks in China were the Iranian-speaking tribes in the eastern part of the Pamir Plateau. Ancient Tashkurgan was a stronghold of economic and cultural exchanges between the East and the West, and on the plateau known as the “Roof of the World”, the Tajiks’ ancestors gradually developed their own unique cultural charms in the course of ongoing exchanges. The first part of this essay focuses on a brief description of the origin and history of the Tajiks in China, from the second century BC to the present. The second part briefly describes the religious beliefs of the Chinese Tajiks, from the beginning of Zoroastrianism, to the later introduction of Buddhism, and up to the present day Islam. The third part briefly describes Tajik music. The author divides Tajik music into four parts: folk songs, folk instrumental music, folk songs and dances, and music for religious ceremonies. The author summarised the characteristics of Tajik music after nearly two months of investigation and research in Tashkurgan Tajik Autonomous County in Xinjiang in 2023, combining the findings of some other scholars.